2006
DOI: 10.1534/genetics.106.060889
|View full text |Cite
|
Sign up to set email alerts
|

Repair of DNA Damage Induced by Bile Salts in Salmonella enterica

Abstract: Exposure of Salmonella enterica to sodium cholate, sodium deoxycholate, sodium chenodeoxycholate, sodium glychocholate, sodium taurocholate, or sodium glycochenodeoxycholate induces the SOS response, indicating that the DNA-damaging activity of bile resides in bile salts. Bile increases the frequency of GC / AT transitions and induces the expression of genes belonging to the OxyR and SoxRS regulons, suggesting that bile salts may cause oxidative DNA damage. S. enterica mutants lacking both exonuclease III (Xth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(135 citation statements)
references
References 86 publications
6
127
0
Order By: Relevance
“…Previous studies had shown that exposure of S. enterica to bile salts induces the SOS response (39,40). To investigate whether suppression of bile sensitivity by asmA mutations was accompanied by reduced bile-induced DNA damage, induction of the SOS system was monitored using a cea::lacZ fusion carried on pGE108 (47).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had shown that exposure of S. enterica to bile salts induces the SOS response (39,40). To investigate whether suppression of bile sensitivity by asmA mutations was accompanied by reduced bile-induced DNA damage, induction of the SOS system was monitored using a cea::lacZ fusion carried on pGE108 (47).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms employed by Escherichia coli and Salmonella enterica to survive in the presence of bile are diverse and only partially understood (18) and involve a variety of cell functions: envelope structures that provide physical barriers to bile salts (31,45,55), efflux pumps that transport bile salts outside the cell (34,38,46,52), and DNA repair functions that maintain genome integrity (39,40). Resistance to bile is especially relevant in Salmonella physiology, since systemic infection leads to colonization of the hepatobiliary tract (35), where the concentration of bile is high and steady (23).…”
mentioning
confidence: 99%
“…These facts could explain why RpoS does not affect mutagenesis in LT2. In contrast, a pathogenic S. enterica strain, expected to express RpoS normally (42,43), displayed DSB repairprotein DinB-, SOS-, and RpoS-dependent SIM when exposed to bile (a stressor) and induced bile-resistant mutants (46,47). Thus, use of DSB repair-protein-RpoS-, SOS-, and DinB-dependent mutation appears to occur in Salmonella but, as expected, to be confined to strains with functional RpoS.…”
Section: Dsb-dependent Stress-induced Mutagenesis In Wild-type Strainmentioning
confidence: 99%
“…bacterial cell membranes due to the detergent activity of bile acids (Begley et al, 2005), causes DNA damage (Prieto et al, 2004(Prieto et al, , 2006 and alters the conformation of proteins. Salmonella, however, resists bile through different mechanisms.…”
Section: Bilementioning
confidence: 99%
“…The genes encoding these proteins are regulated by the transcriptional regulator RamA, which is synthesized in response to bile (Baucheron et al, 2014). In addition, bile-induced DNA damages can be repaired by Dam-directed mismatch repair and by base excision repair, and the impairment of DNA replication rescued by SOS-dependent translation DNA replication and RecBCD-dependent recombinational repair (Prieto et al, 2006). Finally, Salmonella is also able to adapt to grow in extremely high bile concentrations if previously exposed to sublethal doses.…”
Section: Bilementioning
confidence: 99%